2019
DOI: 10.1002/ajmg.c.31692
|View full text |Cite
|
Sign up to set email alerts
|

Genetic landscape of RASopathies in Chinese: Three decades' experience in Hong Kong

Abstract: RASopathies are a group of genetic disorders due to dysregulation of the RAS‐MAPK signaling pathway, which is important in regulating cell growth, proliferation, and differentiation. These include Noonan syndrome (NS), Noonan syndrome with multiple lentigines (NSML), cardiofaciocutaneous (CFC) syndrome, and Costello syndrome (CS), clinical manifestations include growth retardation, developmental delay, cardiac defects, and specific dysmorphic features. There were abundant publications describing the genotype a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Citations for Table 1: Tidyman and Rauen (); Aoki et al (); Yamamoto et al (); Tajan, Paccoud, Branka, Edouard, and Yart (); Yu et al ().…”
Section: Noonan Syndrome and The Rasopathiesmentioning
confidence: 99%
“…Citations for Table 1: Tidyman and Rauen (); Aoki et al (); Yamamoto et al (); Tajan, Paccoud, Branka, Edouard, and Yart (); Yu et al ().…”
Section: Noonan Syndrome and The Rasopathiesmentioning
confidence: 99%
“…The study includes 192 Chinese patients with Noonan syndrome and various forms of rasopathies with molecular confirmation by sanger sequencing. The findings highlight clinically significant phenotype and genotype differences seen in Asian patients that were not present in the literature focusing on Western patients (Yu et al, ). This study adds to the international efforts to describe syndromes including Noonan syndrome in more diverse populations with the goal of creating a universally accessible electronic Altas of human malformation syndromes in diverse populations (Kruszka et al, ).…”
Section: Clinical Genetics In the Genomic Era Studies In Asian Populamentioning
confidence: 55%
“…Further drawing attention to rare diseases that are known to be heterogenous but lack detailed description in minority populations is an analysis of rasopathies by Yu et al This article presents the largest cohort of rasopathies ever reported in Chinese populations, detailing the mutation spectrum and clinical phenotypes of these patients (Yu et al, ). The study includes 192 Chinese patients with Noonan syndrome and various forms of rasopathies with molecular confirmation by sanger sequencing.…”
Section: Clinical Genetics In the Genomic Era Studies In Asian Populamentioning
confidence: 99%
“…Taken together, the RASopathies represent one of the most prevalent groups of malformation syndromes affecting greater than 1 in 1,000 individuals equally distributed in females and males [ 6 ]. While most individuals with RASopathies share characteristic findings affecting multiple organ systems, the phenotypic spectrum is wide, ranging from a mild or attenuated phenotype to a severe phenotype with infantile lethal complications [ 8 ]. Furthermore, less major clinical features were recognized in neonatal or infantile period [ 9 ] than the manifestations in toddlerhood and beyond.…”
Section: Introductionmentioning
confidence: 99%